PRISMA for Abstracts: reporting systematic reviews in journal and conference abstracts. - Beller, E; Glasziou, P; Altman, D; Hopewell, S; Bastian, H; Chalmers, I; Gøtzsche, P; Lasserson, T; Tovey, D (Public Library of Science, 2013)
Elaine Beller and colleagues from the PRISMA for Abstracts group provide a reporting guidelines for reporting abstracts of systematic reviews in journals and at conferences.